Evaluating the Role of Goal Setting in Reducing Dropout for Men With and Without Substance Use Problems Attending a Court-Mandated Intimate Partner Violence Perpetrator Program - Expósito-Álvarez, Cristina (Victims & offenders, 2024)
High dropout rates, particularly among intimate partner violence (IPV) perpetrators with alcohol and other drug use problems (ADUPs), challenge IPV perpetrator programs’ effectiveness. This study sought to examine factors associated with goal setting, a motivational strategy to promote engagement, in a sample of IPV perpetrators (n = 285), including participants with ADUPs (n = 127) and investigated whether goal setting predicted lower dropout by adjusting for relevant variables. Results revealed goal setting could be an effective strategy to reduce dropout in IPV perpetrators and those with ADUPs and support the need to tailor interventions to participants’ needs to enhance effectiveness.